Obesity – should we revise indications for treatment with metformin? - Kujawska-Luczak, Magdalena; Stankowiak-Kulpa, Hanna; Swora-Cwynar, Ewelina; Musialik, Katarzyna; Bogdański, Paweł; Suliburska, Joanna; Grzymisławski, Marian (Menopause Review/Przegląd Menopauzalny, 2014)
Introduction : Treatment of obesity with life style modifications often fails; therefore pharmacological treatment has become a very popular approach. Metformin is one of the examined possibilities. The aim of this study was to verify indications for metformin use in obese women based on metabolic and anthropometric parameters assessed by dual-X-ray absorptiometry (DXA), to establish the degree of insulin resistance and its correlations. Material and methods: Anthropometry, fat measurement by bioimpedance and metabolic profile, including lipids, and oral glucose tolerance test (OGTT) with insulin (0 and 120 min) were performed in 50 female patients diagnosed with simple obesity, aged 18-40 years. Homeostatic model assessment HOMA-R was calculated for insulin resistance, and area under the curve (AUC) for insulin response. Total, android and gynoid fat distribution, and their ratio (A/G), were measured by DXA. Results : From 50 women who entered the study, 33 were classified as insulin resistant (IR subgroup) and 17 as non-insulin resistant (non-IR subgroup), according to their HOMA-R indices. IR women presented higher waist circumference and DXA A/G ratio. The IR subgroup demonstrated elevated fasting triglycerides and glucose (but in the normal range) and a higher insulin response in OGTT (4.1-fold vs 2.5-fold). From different insulin measurements HOMA index turned out to have the strongest correlations with the metabolic parameters triglycerides and glucose. We found significant positive correlations between android fat and insulin: waist circumference and HOMA-R, WHR and HOMA-R, android fat and HOMA-R, A/G ratio and insulin after OGTT, and A/G ratio and HOMA-R. We found a strong correlation between WHR and A/R ratio. Conclusions : 67% of premenopausal obese women were insulin resistant. Measures of DXA visceral fat determined by android fat percentage and android/gynoid ratio were the strongest determinants of insulin resistance. Waist-to-hip ratio might be a simple method for determining the indications for metformin treatment.